E-SERVICE QUALITY EFFECT TOWARD CONSUMER ATTITUDE THROUGH CONSUMER SATISFACTION ON SHOPEE APPLICATION - M. Thoha Ainun Najib; Silky Roudhotus Sa’adah; Rizky Listyono Putro (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This research to analyze the effect of e-service quality toward consumer attitude through consumer satisfaction on Shopee Application in Malang. The research was conducted in Malang with 152 respondents as the sample. This research used Structural Equation Modeling based on Partial Least Square. The research finding showed that there was positive and significant effect of e-service quality toward consumer satisfaction on the Shopee Application. There was positive and significant effect among consumer satisfactions on consumer attitude on Shopee Application. There was positive and significant effect among e-service qualities on consumer attitude on Shopee Application. There was positive and significant effect among e-service qualities on consumer attitude through consumer satisfaction on Shopee Application.